2011
DOI: 10.1007/s00415-011-6279-3
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation response to local cooling in patients with Huntington’s disease

Abstract: Altered autonomic nervous system (ANS) functioning in early stages of Huntington's disease (HD) has been suggested, presumably due to distorted high-order autonomic control. ANS functioning in the early stages of HD was further investigated. Laser-Doppler (LD) flux in the skin of the fingertips, heart rate (HR), HR variability, systolic and diastolic blood pressure were measured during rest and during a 6 min cooling of one hand at 15°C. Data of 15 presymptomatic gene mutation carriers (PHD), 15 early symptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 56 publications
3
23
0
1
Order By: Relevance
“…Cardiovascular and lung phenotypes suggest altered ANS function, being most consistent with increased sympathetic activity at young ages. There is considerable evidence for ANS dysfunction in both manifest and premanifest HD individuals [ 41 , 100 - 105 ]. In HD individuals cardiovascular autonomic tests including blood pressure response to sustained hand-grip, orthostatic blood pressure test, heart rate and heart rate variability at rest and in response to maneuvers or stressors revealed deficits in both the sympathetic and parasympathetic branches of the ANS [ 41 , 100 - 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular and lung phenotypes suggest altered ANS function, being most consistent with increased sympathetic activity at young ages. There is considerable evidence for ANS dysfunction in both manifest and premanifest HD individuals [ 41 , 100 - 105 ]. In HD individuals cardiovascular autonomic tests including blood pressure response to sustained hand-grip, orthostatic blood pressure test, heart rate and heart rate variability at rest and in response to maneuvers or stressors revealed deficits in both the sympathetic and parasympathetic branches of the ANS [ 41 , 100 - 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific setting, LDF has been used to study familial dysautonomia and has helped to understand the relationship between receptors and innervation in autonomic dysfunction [28]. Furthermore, research using LDF in patients with Huntington's disease displaying vasomotor impairment was able to lend evidence to the hypothesized involvement of the autonomic nervous system in the disease's pathophysiology [29].…”
Section: Perspectivementioning
confidence: 99%
“…However, multiple epidemiological studies have shown that heart disease is the second cause of death in patients with HD and the following frequencies have been reported: 12.2% [11], 19% [12] and 24.4% [13]. Moreover, clinical studies have revealed that HD patients have enhanced cardiovagal activity [14], reduced cortical and subcortical blood flow [15] and a reduced heart rate [16]. A further study showed a significant decrease in the parasympathetic heart rate variability values during ‘head-up tilt’ indicating a decreased vagal modulation of heart rate in HD patients.…”
Section: Introductionmentioning
confidence: 99%